(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Countries all across the world have been placed under lockdown as a result of the unexpected emergence of the worldwide health disaster known as the Coronavirus Disease (or COVID-19). The crisis has also put the world's educational systems under strain, forcing academics to switch from face to face to online learning. Open and Distance Learning (ODL) method is one of the most suitable strategies that integrates virtual technology which consequently allows the continuation of the teaching and learning process. As an open university that already has ODL, learning methods and student service should be more robust. Quantitative research was conducted using a 34-item questionnaire to explore the challenges students face in the context of online learning; and to identify the student’s preferences for their convenience for the adoption of quality improvement in online learning. Data was collected from sixty-four (64) postgraduates students enrolled in the Faculty of Technology and Applied Sciences, Open University Malaysia. The study revealed that staying motivated and engaged in online classes, with a Relative Importance Index (RII) of 0.6188, stands out as the most significant challenge for the students. On a positive note, the availability of clear learning objectives, with the highest RII of 0.8188, emerged as the top preference among students for adopting quality improvement in online learning. These findings underscore the importance of addressing motivational factors and emphasising clear learning objectives to enhance the overall online learning experience.